AusArray: Toward updatable, high-resolution seismic velocity models of the Australian lithosphere. Issue 1 (1st December 2019) - Gorbatov, Alexei; Czarnota, Karol; Haynes, Marcus; Hassan, Rakib; Hejrani, Babak; Zhao, Jason; Salmon, Michelle; Sambridge, Malcolm; Tkalčić, Hrvoje; Yuan, Huaiyu; Rawlinson, Nicholas; Reading, Anya M.; et al.
Summary: In order to improve exploration success under cover the UNCOVER initiative identified high resolution 3D seismic velocity characterization of the Australian plate as a high priority. To achieve this goal government and academia have united around the Australian passive seismic Array project (AusArray) which aims to obtain a national half degree data coverage and an updateable 3D national velocity model which grows in resolution as data become available. AusArray unites data collected from the Australian National Seismological Network (ANSN), multiple academic transportable arrays (supported by AuScope and individual grants) as well as the seismometers in schools program. A recent addition has been Geoscience Australia's Exploring for the Future program (EFTF) which has doubled the national rate of such data collection. Extensive quality-control checks have been applied across this combined dataset to improve the robustness of subsequent tomographic inversion and interpretation. The aim being an updatable national velocity reference model with resolution from depths of a few meters to hundreds of kilometres. The first stage of lithospheric seismic modelling has been the development of P and S body-wave tomography models. An initial earthquake catalogue of ~26, 000 events, dating from 1993 to present, has been developed. This is used to estimate first-arrival times using high-performance routines on the National Computational Infrastructure supercomputer facility. Obtained parametric data were then used in non-linear tomographic inversion with a realistic wave propagation scheme. Resulting P and S tomographic images show a strong correlation with major crustal and lithospheric mantle boundaries. Vp and Vs variation patterns are not always positively correlated thereby providing new insights into the architecture of the Australian plate. Integration with resistivity models derived from magnetotelluric data provide insights into the control of minor phase distribution on the imaged architecture.